Transfer of 238U, 230Th, 226Ra, and 210Pb from soils to tree and shrub species in a Mediterranean area. - Blanco Rodríguez, P.; Vera Tomé, F.; Lozano, J. C.; Pérez Fernández, M. a (Applied radiation and isotopes : including data, instrumentation and methods for use in agriculture, industry and medicine, 2010)
The soil-to-plant transfer factors of natural uranium isotopes ((238)U and (234)U), (230)Th, (226)Ra, and (210)Pb were studied in a disused uranium mine located in the Extremadura region in the south-west of Spain. The plant samples included trees (Quercus ilex, Quercus suber, and Eucalyptus cameldulensis) and one shrub (Cytisus multiflorus). All of them are characteristic of Mediterranean environments. The activity concentrations in leaves and fruit were determined for the tree species at different stages of growth. For the shrub, the total above-ground fraction was considered in three seasons. For old leaves and fruit, the highest activity concentrations were found in Eucalyptus cameldulensis for all the radionuclides studied, except in the case of (230)Th that presented similar activity concentrations in all of the tree species studied. In every case, the transfer to fruit was less than the transfer to leaves. In the shrub, the results depended on the season of sampling, with the highest value obtained in spring and the lowest in autumn. Important correlations were obtained for (238)U and (226)Ra between the activity ratio in soils with that in leaves or fruit.
The following values have no corresponding Zotero field: accession-num: 20153657
Keywords: Arboreal species; Fruit; leaves; Natural radionuclides; Soil-to-plant transfer factors